Neuroimaging correlates of disability in Motor Neuron Disease - Tahedl, Marlene (Trinity College Dublin. School of Medicine. Discipline of Clinical Medicine, 2024)
Motor neuron diseases (MND) clinically present with a wide variety of motor and extra-motor symptoms. However, the pathological correlates of such symptom manifestation and their progression is poorly understood. In the series of studies comprising this thesis, we used novel multimodal neuroimaging metrics to characterise both the cross-sectional and longitudinal manifestation of both types of neurological deficits. We investigated multimodal magnetic resonance imaging (MRI) data from different types of MND disorders, including amyotrophic lateral sclerosis (ALS, and ALS variants, such as ALS-frontotemporal dementia, FTD), and primary lateral sclerosis (PLS), and investigated derived MRI metrics both at baseline and their progression across multiple follow-up assessments. To understand the potential clinical impact of the observed changes, we used rich neuropsychological and clinical assessments to analyze associations. In all studies, multimodal neuroimaging metrics were investigated in MND, whereas the first two studies focus on ALS (and variants) as the most common MND disorder, and the remaining two studies focus on PLS as a relatively rare MND. Whereas the motor system was targeted in the first two studies, extra-motor systems were targeted in the remaining two studies. The current study series provides evidence that multimodal neuroimaging sensitively captures motor and extra-motor involvement in MND. This sensitivity was demonstrated multifold, including for (i) common (ALS) and uncommon (PLS, ALS-FTD) MND disorders and (ii) cross-sectional and longitudinal assessments, as well as (iii) (i) motor and extra-motor symptoms, including language deficits and pseudobulbar affect (PBA). Our academic study results provide compelling evidence that multimodal neuroimaging metrics can further enhance future clinical trial protocols. Although such deficits have severe impacts on patients? quality of life and implications for caregivers, they are hardly taken into account as outcome measures in clinical trial protocols, probably because quantitative and standardized assessment has not yet been convincingly demonstrated. With our results, however, we believe to have provided such evidence and thereby hope to contribute to the integration of multimodal neuroimaging into the design of clinical trials, ultimately motivating the development of therapeutics specifically targeted at such severely the quality of life impairing symptoms in MND.
APPROVED
Keywords: neuroimaging; magnetic resonance imaging; tractography; pseudobulbar affect; motor neuron disease